A very unusual case of attempted suicide - Misiak, Piotr; Jabłoński, Sławomir; Dziwińska, Katarzyna; Terlecki, Artur (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2016)
We would like to present a case report of a very unusual suicide attempt. A 48-year-old female patient tried to commit suicide by stabbing herself with a kitchen knife into her neck. Suicide by self-stabbing is uncommon, constituting only 1-3% of suicide attempts. Patients with self-inflicted stab wounds may have a higher incidence of surgical interventions based on the stab location. Surprisingly, the mortality associated with this kind of wound is low. Most medical centers have very limited experience with this infrequent injury. There are only a few case reports and small series published in the literature of the subject.